Pendampingan Two Stay Two Stray Pengelolaan Makanan Sehat Untuk Penguatan Literasi Keuangan dan Mencegah Fomo Kuliner Generasi Z SAS English Laboratory - Rizqy Fadhlina Putri; Nur Asyah; Rini Fadhillah Putri (LPPI UMN AL WASHLIYAH, 2025)
This community service is carried out through mentoring activities for SAS English Laboratory tutors, 89% of whom are Generation Z. The current habits and the ease of social media have poisoned the mindset of Generation Z to experience